2020
DOI: 10.4103/ijmr.ijmr_1722_20
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of SARS-CoV-2 infection among Italian tourists visiting India, March 2020

Abstract: Background & objectives: A cluster of SARS-CoV-2 infection occurred among Italian tourists visiting India. We report here the epidemiological, clinical, radiological and laboratory findings of the first cluster of SARS-CoV-2 infection among the tourists. Methods: Information was collected on demographic details, travel and exposure history, comorbidities, timelines of events, date of symptom onset and duration of hospitalization from the 16 Italian tourists and an India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…To avoid age-dependent bias in asymptomaticity, we removed studies where all participants belonged to a single age class (children, adults, or the elderly). Out of the 25 studies selected, 7 studies performed screening of all close household contacts ( 64 , 80 , 83 , 103 , 117 , 131 ), 3 screened all flight passengers ( 28 , 84 , 91 ), and 2 screened all members of a tourist/pilgrim group ( 94 , 129 ). Others were based on screening of healthcare workers ( 25 , 110 ), inpatients admitted for non−COVID-19 reasons ( 19 , 50 , 59 , 72 , 108 , 113 ), rigorously community screening ( 82 , 166 ), travelers ( 18 , 180 ), and those associated with a detention facility ( 92 ).…”
Section: Methodsmentioning
confidence: 99%
“…To avoid age-dependent bias in asymptomaticity, we removed studies where all participants belonged to a single age class (children, adults, or the elderly). Out of the 25 studies selected, 7 studies performed screening of all close household contacts ( 64 , 80 , 83 , 103 , 117 , 131 ), 3 screened all flight passengers ( 28 , 84 , 91 ), and 2 screened all members of a tourist/pilgrim group ( 94 , 129 ). Others were based on screening of healthcare workers ( 25 , 110 ), inpatients admitted for non−COVID-19 reasons ( 19 , 50 , 59 , 72 , 108 , 113 ), rigorously community screening ( 82 , 166 ), travelers ( 18 , 180 ), and those associated with a detention facility ( 92 ).…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria were articles with an index case or cases whose infectious period was during the flight and articles with identification of close contacts tested for COVID-19 within the 14-day incubation period following the flight. This resulted in a total of 19 articles [3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The denominator in calculated attack rates included the susceptible flight contacts, excluding those already confirmed as or infectious with COVID-19 at the time of the flight.…”
Section: Methodsmentioning
confidence: 99%
“…Our significant findings of a highly significant association between AR and CFR is supported by the following previous observations: (1) available data about South Americans and Asian countries that took the strictest measures, and they also had relatively lower COVID-19 CFR 6,17 , (2) it has been noticed that in European countries that have had both large numbers of cases and deaths 15 , the average of country-specific CFR was at 0.7% –1.3% at early times of pandemic raised to about 2%–3.31%D thereafter 6 , this increase in Covid-19 CFR possibly goes in parallel with an increase in number of cases, (4) the CFR of COVID-19 differs by location, and has changed during the period of the outbreak 3,6 , (5) small clusters of fatal COVID-19 infections were reported previously with high CFR within these clusters (families, tourists, long□term care hospitals and facilities, etc.). 18, 19,20,21,22 There were also identified “vulnerable” clusters of counties in USA with high mortality incidence ratio. 23 In UK A few areas saw COVID-19 mortality more than seven times the expected level compared with the rest of the country 24 , (6)association between population size and COVID-19 CFR 6 , and (7) our findings were in concordance with recent studies which found very high positive significant correlation between total deaths/1M and the total number of cases and a very high positive influence of the COVID-19 MR on the CFR 11,12 .…”
Section: Discussionmentioning
confidence: 99%
“…,this increase in Covid-19 CFR possibly goes in parallel with an increase in number of cases, (4) the CFR of COVID-19 differs by location, and has changed during the period of the outbreak 3,6 , (5) small clusters of fatal COVID-19 infections were reported previously with high CFR within these clusters (families, tourists , long term care hospitals and facilities, etc.). 18,19,20,21,22 There were also identified "vulnerable" clusters of counties in USA with high mortality incidence ratio. 23 In UK A few areas saw COVID-19 mortality more than seven times the expected level compared with the rest of the country 24 , (6)association between population size and COVID-19 CFR 6 , and (7) our findings were in concordance with recent studies which found very high positive significant correlation between total deaths/1M and the total number of cases and a very high positive influence of the COVID-19 MR on the CFR 11,12 .…”
Section: Our Significant Findings Of a Highly Significant Association Between Ar And Cfr Is Supported By The Following Previous Observatimentioning
confidence: 99%